If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -11 = 4x + 19 Reorder the terms: -11 + -6x = 4x + 19 Reorder the terms: -11 + -6x = 19 + 4x Solving -11 + -6x = 19 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -11 + -6x + -4x = 19 + 4x + -4x Combine like terms: -6x + -4x = -10x -11 + -10x = 19 + 4x + -4x Combine like terms: 4x + -4x = 0 -11 + -10x = 19 + 0 -11 + -10x = 19 Add '11' to each side of the equation. -11 + 11 + -10x = 19 + 11 Combine like terms: -11 + 11 = 0 0 + -10x = 19 + 11 -10x = 19 + 11 Combine like terms: 19 + 11 = 30 -10x = 30 Divide each side by '-10'. x = -3 Simplifying x = -3
| 45-3(n)=5+n | | x(x+10)+24=0 | | 4=0.5-4 | | p(0)=-2x^3+8x-6 | | 6x+17=8x+1 | | -|16|?16= | | 2(8x)+44x=180 | | (8x^2-3x^3)-(6x^2-5x^3)= | | -6y+11=-2x+11 | | 41-2n=2+9 | | -4t^2+766=200 | | 0=-2x^3+8x-6 | | 7(11x+22)+x=-10x | | (3x^4+5y^2)(7x^4+5y^2)= | | 4n-28=2+9n | | -x^2-20x-19=0 | | y=-6/5-2 | | 3-3z=21 | | 8z-8=48+z | | 8(x-4)=7y-38 | | 7x+(5-x)3=12+15 | | 2x*3x*4xy= | | 34346920357904578096870945807824507809548709845097824057284507928049578094804380934580982450978109348091834091834709870743+3296834986723986729834769345876x=34576384563837658375687684536-39475298374698374589649537698457896x | | 4=160 | | 1r+8.2+0.4=-8.6 | | 1=0x+1 | | 182.12=2r*3.14 | | -6x-24=-144 | | 8.93/4.44=4.49/n | | 9X=3-6Y | | Y=4f(-x)-23 | | e^4lnx=6 |